(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the severity of tic disorders using the Yale Global Tic Severity Scale (YGTSS) and to examine factors associated with tic severity among children attending the National Children’s Hospital in 2025. Subjects and methods: A cross-sectional descriptive study was conducted on 176 patients under 18 years of age diagnosed with tic disorders according to ICD-10 criteria. All participants had not received pharmacological or psychological treatment for tic disorders prior to enrollment. Tic severity was assessed using the YGTSS. Data were managed and analyzed using RStudio software. Results: Boys accounted for 75% of the sample, with a male-to-female ratio of 3:1. The mean age at diagnosis was 6.60 ± 2.63 years. Most patients were diagnosed with transient tic disorder (72.2%). The mean Total Tic Severity Score was 16.34 ± 7.01, the mean impairment score was 16.64 ± 6.62, and the mean global YGTSS score was 30.0 ± 11.2. No significant difference in tic severity was found between sexes. Age at diagnosis and duration of illness were positively associated with tic severity. Children with comorbid conditions, particularly attention-deficit/hyperactivity disorder, autism spectrum disorder, had significantly higher YGTSS scores than those without comorbidities (p < 0.05). Conclusions: Tic disorders in children present with varying degrees of severity and functional impairment. The YGTSS is a valuable tool for comprehensive assessment of tic severity and functional impact. A holistic approach to the evaluation and management of tic disorders, including early detection and assessment of comorbid conditions, is essential to reduce clinical burden and improve outcomes.